Evaluation of Zirconia Surfaces after Strong-Acid Etching and Its Effects on the Shear Bond Strength of Dental Resin Cement - Yongsang Lee; Kyung Chul Oh; Na-Hong Kim; Hong-Seok Moon (International Journal of Dentistry, 2019)
The present study was intended to investigate changes in the microstructure and phase transformation of zirconia surfaces using etching and airborne-particle abrasion (AB) and the effects of these processes on the shear bond strength of dental resin cements to zirconia. Four groups were classified according to the surface treatment as follows: etching for 15 min (ET15), etching for 30 min (ET30), AB, and etching for 15 min following AB (ABET). These groups were then classified into two subgroups (a total of 8 groups with 11 specimens/group) according to the resin cement used for bonding, namely, Rely-X U200 (3M ESPE, St. Paul, MN, USA) or Panavia F 2.0 (Kuraray, Kurashiki, Okayama, Japan). Shear bond strength testing was performed using a universal testing device. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were also performed. When using Rely-X U200, ET15 exhibited the highest mean shear bond strength; the strengths of ET15, ABET, and ET30 were significantly higher than that of AB. When using Panavia F 2.0, ABET demonstrated the highest mean shear bond strength; the strengths of ABET and ET15 were significantly higher than those of ET30 and AB. The etched surface of zirconia could be observed using SEM, and the phase transformations resulting from each surface treatment were detected by XRD. Strong-acid etching of zirconia induced significant surface changes that increased the shear bond strength of resin cement, and the resin adhesive strength was higher when zirconia was etched with strong acid vs. AB alone.